Diglossic situation in sorani kurdish dialect - Kawar Mohammed Sanaddin; Wrya Izzadin Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Diglossia is a sociolinguistic phenomenon that has deduced the interest of many sociolinguists. The first linguist is Ferguson (1959) who introduced the concept of diglossia to explain the distribution of naturally related varieties in different situations of the same speech community. One is a standard language where it is used as formal language in written and spoken communities and it is mainly learned in the way of education. While the other variety is used for normal interaction and communication. This is an attempt to investigate the diglossic situation of Sorani Kurdish dialect in Iraqi Kurdistan Region. Also of the problematic situation of using formal language in official institutions and informal language for daily communication.